Screening of magnetotactic bacteria from lakes in Universiti Sains Malaysia, Penang / Nurulatika Minhad - Minhad, Nurulatika (Universiti Teknologi MARA Cawangan Pahang, 2020)
Magnetotactic bacteria (MTB) is a Gram-negative prokaryote which depends on the magnetic influence called magnetotaxis imposed upon them. MTB produces intracellular encased magnetic grains, magnetosomes. The bacteria are hard to isolate in axenic culture due to its fastidious lifestyle. The objective of the study is to screen water samples from two lakes in Universiti Sains Malaysia (USM), Penang for magnetotactic bacteria. Approximately 500 microliter (ml) of samples were collected in triplicates and incubated in the dark for 2 days. For isolation of MTB, a modified method of racetrack purification, hanging drop and centrifugation technique of MTB were used. The samples were enriched in a modified medium and incubated in a shaker incubator for one week. Pour plate and streak plate methods were done. For characterization, microscopic analysis using optical and scanning electron microscope (SEM) was carried out to observe swimming behaviour of MTB and its magnetosomes if any. The screening of MTB showed that all the samples were Gram-negative but there was no movement of bacteria towards magnetic force and no magnetosomes found. Therefore, it can be assumed that water samples from the two lakes in USM do not have magnetotactic bacteria due to its fastidious growth, hard to isolate in axenic culture and exists in a place with abundant of soluble ferrous form.